Chemical synthesis of magnesium oxide (MgO) from brine towards minimal energy consumption - Chu, S. H (2023)
The precipitation of magnesium from marine-derived feedstocks (e.g. waste brine discharged from desalination plants), has several environmental and economic advantages, if the right conditions are provided. In this work, the synthesis of reactive magnesium oxide (MgO) from the feedstock of simulated waste brine was demonstrated. One of the main challenges is the high energy consumption during the calcination of brucite, requiring the optimization of the calcination process to reduce this energy demand. To investigate this aspect, different calcination temperatures (400–550 °C) and durations (1−2 h) were examined and the synthesized MgO was evaluated for its chemical composition, specific surface area (SSA), reactivity and microstructure. The obtained results revealed the critical calcination condition that distinguished between low and high reactivity MgO, which also differentiated between plate-like and fiber-like morphology of MgO. Optimization of the calcination conditions led to SSA values as high as 167 m2/g. Calcination conditions with a minimum energy demand were identified for achieving MgO powders with a high reactivity, high SSA, and morphologies with a high propensity for hydration and/or carbonation reactions.